New Outreach Initiatives at a Community College. Issue 3 (2nd October 2017) - Walker, Sharell L.
Abstract: This article explores the development and initiation of new outreach programs by the Borough of Manhattan Community College (BMCC) Library department after the hiring of a new librarian. The literature review will address current research that was used in the decision making process whilst putting together outreach initiatives and literature used to develop future ideas. The article discusses the development of these outreach initiatives, the problems encountered during their initial implementation, the outcomes of the programs that were offered, feedback, and the future goals of the library department.